2018
DOI: 10.1186/s13014-018-1062-6
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal DIBH reduces the cardiac dose even further: a prospective analysis

Abstract: BackgroundDeep inspiration breath hold (DIBH) can be performed using different breathing maneuvers, such as DIBH with a thoracic breathing maneuver (T-DIBH) and DIBH with an abdominal breathing maneuver (A-DIBH). Dosimetric benefits of A-DIBH were investigated in the treatment of left-sided breast cancer radiotherapy (RT) with both 3-Dimensional conformal radiation therapy (3D-CRT) and intensity-modulated radiotherapy (IMRT) techniques.MethodsTwenty-two patients with left-sided breast cancer were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 31 publications
11
34
0
1
Order By: Relevance
“…This study compared the dosimetric results obtained from six treatment plans (FB 3D-CRT , FB IMRT , FB VMAT , aDIBH 3D-CRT , aDIBH IMRT , and aDIBH VMAT ) for left-sided breast cancer patients undergoing IMC-inclusive PMRT. We found that with aDIBH, the doses to the heart and LAD were substantially decreased regardless of the treatment plan (3D-CRT, IMRT, and VMAT), which is consistent with our previous study we first proposed using aDIBH to reduce the cardiac dose further (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study compared the dosimetric results obtained from six treatment plans (FB 3D-CRT , FB IMRT , FB VMAT , aDIBH 3D-CRT , aDIBH IMRT , and aDIBH VMAT ) for left-sided breast cancer patients undergoing IMC-inclusive PMRT. We found that with aDIBH, the doses to the heart and LAD were substantially decreased regardless of the treatment plan (3D-CRT, IMRT, and VMAT), which is consistent with our previous study we first proposed using aDIBH to reduce the cardiac dose further (18).…”
Section: Discussionsupporting
confidence: 91%
“…Understandably, one study reported significant movement of the lymph node areas due to DIBH, which implies a larger internal target volume (ITV) is needed to compensate for the movement (17). Our previous study found that by reducing the thoracic proportion as much as possible, aDIBH could further decrease the cardiac dose (18) because the significantly lowered heart position keeps it further away from the clinical target volume (CTV).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the OAR, the heart, all dosimetric parameters (including the mean dose, D2%, V 5 , and V 10 ) showed a better performance with DIBH-VMAT than with FB-VMAT, similar to a previous study ( 32 , 33 ). As early as 2005, Korreman et al ( 34 ) published a result about nine left-sided breast cancer patients with RT, showing that DIBH substantially reduced the doses to the heart and lung.…”
Section: Discussionsupporting
confidence: 87%
“…9,[14][15][16] While it has been recognized that a learning curve exists for patients to acquire the complex physical and cognitive skills to perform DIBH manoeuvres well, 17 only very few studies have explored alternative preparatorytraining approaches to boost patients' DIBH performance and tolerance. 13,[18][19][20][21] Logistically the timing of respiratory training can be expanded farther into the pre-radiation therapy phase, enabling earlier, preparatory and thereby more intensified DIBH training regimens that provide longer time for patients to practice and improve their DIBH skills. Results of these very few studies show promise that a strategy of early preparatory DIBH training and practice, implemented well in advance of the first DIBH performance at the simulation procedure, can measurably decrease procedure time spent in CT simulation, 13 lengthen the sustained DIBH 19,20 and broaden the range of breath-hold manoeuvres performed.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these very few studies show promise that a strategy of early preparatory DIBH training and practice, implemented well in advance of the first DIBH performance at the simulation procedure, can measurably decrease procedure time spent in CT simulation, 13 lengthen the sustained DIBH 19,20 and broaden the range of breath-hold manoeuvres performed. 21 Among these investigations, our previous comparison study was the first to demonstrate that cardiac dose can be further reduced by in-advance preparatory DIBH training and practice. 18 Patients who received preparatory DIBH coaching, training and home practice for 1-2 weeks before the CT simulation, had significantly lower cardiac dose (max dose: 13.1 vs. 19.5 Gy, P = 0.004) than those with conventional immediate pre-procedure instruction, based on dosimetry from CT simulation imaging.…”
Section: Introductionmentioning
confidence: 99%